Child Presence Detection Car Alarm System using GSM - AHAD, ROSNEE; Rosli, Nur Suhaila; Mustafa, Mohamad Zaid (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: Various cases of child deaths occurred in the country, in 2018 and 2019 there were three deaths involving children drowning and suffering from stroke due to being left in the car. The purpose of this study is to design, develop and evaluate the functionality of Child in Car Detector with Alarm and Notification System using GSM. The researcher used an Engineering Design Process as a design model approach. Arduino UNO is used to control the system receiving input from key switches and relays then from the load cell detector then instructs buzzer 1 to sound and Global System for Mobile Communication will send a message to the car owner and buzzer 2 will sound if there are still children in the car. Three experts have evaluated this product for possible improvements that can improve the quality of this product to work better and efficiently and also can help to reduce the number of children being left in the cars. Keywords: A child being left in the car, Car Detector, Alarm and Notification System, GSM.